Transmigration of Highly Qualified Personnel – A Challenge for Human Resources Management - Andreas Siegert (Foresight and STI Governance)
Ability to attract and retain highly qualified personnel is a key factor of competitiveness. This is a serious challenge for companies, and especially research organizations that do not have the capacity in terms of human resource management. The migratory behavior of highly qualified professionals is changing due to unprecedented employment and career development opportunities that have appeared as a result of globalization. Today when choosing a potential employer not only financial interests, but the proximity of mentality and the general cultural background of countries of origin and residence come to the fore. Most experts agree that the mobility of professionals is dictated by some homogeneous interests. However, analysis of the migratory behavior of Russian scientists-transmigrants in Germany refutes this assertion.